Pós-desenvolvimento, indicadores e culturas de auditoria: reflexões críticas sobre governança e desenvolvimento - Guilherme Francisco Waterloo Radomsky (Ciências Sociais Unisinos)
The article explores three dimensions of the recent debate on development. Firstly, it briefly analyzes the critique of development in the proposal that became known as post- development. Secondly, the possible connection between post-development and the critical analysis of indicators, rankings and standardized goals for development and governance is examined. Finally, we analyze the complex and disputed relationship between coloniza- tion and development. As a conclusion, the article rethinks contemporary social theory and related issues from development studies, as agency and auditing, peoples’ desire/ repulsion for development projects and the critique of modernity.